2014
DOI: 10.1016/j.ebiom.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An Endotoxin Tolerance Signature Predicts Sepsis and Organ Dysfunction at Initial Clinical Presentation

Abstract: BackgroundSepsis involves aberrant immune responses to infection, but the exact nature of this immune dysfunction remains poorly defined. Bacterial endotoxins like lipopolysaccharide (LPS) are potent inducers of inflammation, which has been associated with the pathophysiology of sepsis, but repeated exposure can also induce a suppressive effect known as endotoxin tolerance or cellular reprogramming. It has been proposed that endotoxin tolerance might be associated with the immunosuppressive state that was prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 35 publications
5
138
0
4
Order By: Relevance
“…Transcriptomic features of endotoxin tolerance and pathway enrichment for cell death, apoptosis, necrosis, and T-cell exhaustion are consistent with animal models and human studies demonstrating the importance of immune compromise in sepsis pathogenesis and as a determinant of poor outcomes (4,31,32). The FP dataset allowed us to explore evolution of SRS membership.…”
Section: Discussionmentioning
confidence: 82%
“…Transcriptomic features of endotoxin tolerance and pathway enrichment for cell death, apoptosis, necrosis, and T-cell exhaustion are consistent with animal models and human studies demonstrating the importance of immune compromise in sepsis pathogenesis and as a determinant of poor outcomes (4,31,32). The FP dataset allowed us to explore evolution of SRS membership.…”
Section: Discussionmentioning
confidence: 82%
“…In support of this hypothesis, an endotoxin tolerance gene signature has been associated with worse patient outcomes (7, 8), and a high incidence of secondary nosocomial infections in critically ill patients (9). Concurrent with this suggestion, an alternative body of literature reports that treatment with TLR4 ligands such as LPS and monophosphoryl lipid A (MPLA), the prototypical ligands used to induce endotoxin tolerance, augments host resistance to infection while facilitating suppressed cytokine production in a variety of infection models (1012).…”
Section: Introductionmentioning
confidence: 90%
“…34 They then used RNA-seq in a validation cohort to show that the endotoxin tolerance signature is more enriched in patients with more severe sepsis at admission (more organ failure) than in less-complicated cases. 35 They further showed that their endotoxin tolerance module can be found in several independent sepsis datasets. This confirms that the immune paralysis/tolerance seen in late critical illness is also present in early severe sepsis, and may contribute to the worse outcomes of high-risk patients.…”
Section: “Immune Paralysis” In Sepsis: An Updated View From Cars To Picsmentioning
confidence: 97%